Annual Plan 2000-01 Orissa Vol.-II - Planning Commission (Planning Commission, 2000)
Proposed Outlays , Physical Targets and Achievements , Proposals for Spillover and ongoing , Programmes / Projects as in Annexure -1 , Proposals for Maximising benefits of completed , Programmes / Projects (As on 31.3.2000 ) , Proposals for Programmes / Projects - New Schemes , Summary Statement - Proposals for , Programmes / Projects , Statement regarding Externally Aided Projects , Outlays ( By Heads of Development) for District Plans.
Planning and Coordination Department, Government of Odisha
Planning and Coordination Department, Government of Odisha